Islamic–Chinese Interaction in Cap Go Meh: Ritual Resistance and Its Contribution to the Sustainable Development Goals (SDGs) - Tjik Harun; Ris’an Rusli; Choirun Niswah; Reza Aprianti (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study aims to examine Islamic–Chinese interaction during the Cap Go Meh celebration on Kemaro Island, Palembang, by analyzing ritual resistance and cultural dialogue as mechanisms for preserving Chinese cultural identity while fostering interreligious coexistence and contributing to the Sustainable Development Goals (SDGs). Theoretical framework: The research is grounded in theories of ritual resistance, symbolic interactionism, and multiculturalism, which explain how religious symbols, collective memory, and cultural negotiation shape social integration within plural societies. Literature review: Previous studies have primarily discussed Cap Go Meh from perspectives of tourism, cultural heritage, or Chinese identity, while limited attention has been given to its role as a site of Islamic–Chinese interaction and its relevance to sustainable development. This study addresses that gap by integrating ritual analysis with the SDGs framework. Method: Employing a qualitative ethnographic approach, data were collected through participant observation, in-depth interviews with community leaders, religious figures, festival participants, and local residents, complemented by documentary analysis. Data were analyzed using thematic interpretation to identify patterns of symbolic interaction, ritual adaptation, and social acceptance. Results: The findings reveal that ritual symbols, including lanterns, lion dances, incense, and the legendary narrative of Siti Fatimah and Tan Bun An, function as adaptive cultural strategies rather than exclusive religious expressions. These symbols facilitate intercultural dialogue, strengthen mutual trust, and transform historical resistance into collaborative social engagement accepted by the surrounding Muslim community. Such interactions reinforce social cohesion, preserve cultural diversity, and support peaceful coexistence. Furthermore, the festival contributes directly to SDG 11 (Sustainable Cities and Communities) by safeguarding cultural heritage and strengthening inclusive communities, and SDG 16 (Peace, Justice, and Strong Institutions) by promoting tolerance, dialogue, and social harmony. Implications: The findings demonstrate that local cultural traditions can serve as practical models for intercultural governance and sustainable community development in multicultural societies. Novelty: This study offers a novel perspective by conceptualizing Cap Go Meh as an adaptive arena of ritual resistance that simultaneously functions as a platform for Islamic–Chinese interaction and a cultural mechanism supporting the achievement of the SDGs.